Risk and Protective Factors of Lifetime Cocaine-Associated Chest Pain - Clergue-Duval, Virgile; Nicolas-Sacy, Louise; Karsinti, Emily; Zerdazi, El-Hadi; Laplanche, Jean-Louis; Brousse, Georges; Marees, Andries T.; Derks, Eske M.; Henry, Patrick; Bellivier, Frank; Vorspan, Florence; Bloch, Vanessa (Frontiers in Psychiatry, 2021)
Introduction: Cocaine users often present with repetitive events of cocaine-associated chest pain (CACP), clinically resembling acute coronary syndromes. The aim of the study is to describe the specific risk factors for CACP. Method: Cocaine users (n=316) were recruited for a multicenter cross-sectional study. Lifetime CACP history, sociodemographic factors, and lifetime use of cocaine and other substances were assessed. Thirty single nucleotide polymorphisms (SNPs) of NOS3, ROCK2, EDN1, GUCY1A3 and ALDH2 genes, suggested by the literature on coronary spasms, were selected. The associations with CACP history were tested using the chi-square test, Student’s t-test and logistic regression. Results: Among the 316 subjects (78.5% men, mean age 37.5 years, [standard-deviation ±8.7]), 190 (60.1%) were daily cocaine users and 103 (32.6%) reported a lifetime CACP history. Among those with a lifetime CACP history, the median was 10 events per individual. In multivariate analysis, lifetime CACP history was associated with daily cocaine use (odds-ratio (OR) 3.24; 95% confidence intervals [1.29-9.33]), rapid route of cocaine use (OR 2.33 [1.20-4.64] versus intranasal use), and lifetime amphetamine use (daily amphetamine use: OR 2.80 [1.25-6.32] and non-daily amphetamine use: OR 2.14 [1.15-4.04] versus never used). Patients with lifetime opioid maintenance treatment (OMT) reported significantly less lifetime CACP history (OR 0.35 [0.16-0.76]). None of the selected SNPs was associated with CACP history after multiple testing corrections. Conclusions: Clinical variables describing the intensity of stimulant use were positively associated with lifetime CACP history, while OMT was negatively associated with it. Specific harm reduction strategies can target these risk factors.